Hubungan Komunikasi Terapeutik Perawat dengan Tingkat Depresi Pasien Glaukoma di Rumah Sakit Tipe C Jember - Rezha Arie Oktavianti (Fakultas Keperawatan, 2026)
Introduction: Glaucoma is a chronic disease of the optic nerve that can cause visual impairment and even blindness. Vision loss due to glaucoma not only impacts physical conditions but can also cause psychological problems such as depression. One factor suspected of being related to the level of depression in glaucoma patients is therapeutic communication carried out by nurses. This study aims to analyze the relationship between nurses' therapeutic communication and the level of depression in glaucoma patients at Jember Type C Hospital. Method: This study used a descriptive correlasional design with a cross-sectional approach. The study sample consisted of 276 glaucoma patients selected using a purposive sampling technique. Data collection was carried out using a therapeutic communication questionnaire and the Patient Health Questionnaire-9 (PHQ-9). Data analysis used the Spearman Rank test with a significance level of α = 0.05. Result: The results showed that the majority of respondents were female (55.8%), elementary school educational background (31.5%), and worked as housewives (32.6%). The majority of nurses' therapeutic communication was in the effective category, with 182 respondents (65.9%). The depression levels of glaucoma patients were dominated by mild depression, with 156 respondents (56.5%). Conclusion: The Spearman Rank test showed a p-value of 0.000 (p < 0.05), indicating a significant relationship between nurses' therapeutic communication and glaucoma patients' depression levels. The more effective the nurses' therapeutic communication, the lower the glaucoma patients' depression levels. This study demonstrates the importance of implementing therapeutic communication as part of nursing care to help reduce depression levels in glaucoma patients.
Reupload file repository 4 Juni 2026_Ratna
Keywords: Therapeutic communication; Depression; Glaucoma.